Ethnic Politics and the Agitation for Restructuring Nigeria: Implication for National Development and Dialogue Initiative - Amiara, Amiara, Solomon; Omeje, Dr Paul Uroku; Nwoikie, Dr Kennth Igbomaka (Archives of Business Research, 2019)
The evolution of NIgerian State is shrouded in cultural complexities that are built on linquistc variations and ethno-religious discontents. Asa a product of the British imperialism, the 1914 amaglmation of the northern and southern protectorates saw the emergence of what became an independent NigerianState on October 1, 1960. Thus, the activities of these imperialists led to the birth of Nigeria’s naionalism which was couched in ethnic nationalism rather than true pan Nigerianism. This ethnocentrism has advertently deepened Nigeria’s problems and led to the evolution of several regime system that manifested into resource control, independent movement and ethnic militants. Scholars and policy-makers alike, have over the last two decades tried several workable political system without actually arriving at any possible solution thereby stoking the flame of ethnic based crises that fraught Nigerian sovereignty. Against this background, the proclamation of the Sovereign State of Biafra was celebrated with attended war that followed therein. Therefore, it is understood that the aftermath of the war still linger and gave birth to Indigenous People of Biafra. While it could be said that the bulk of Nigerian resources are committed to finding solution to the existing political structures, it is obvious that the weighter problems arising from corruption, prebendalism and lack of true federalism that resulted to the evolution of ethnic millitias are still neglected. Therefore, the study identifies corruption, favouritism and nepotism as the majorproblems of ethnic politics in Nigeria while applying thematic, and historical analytical method as a method of analysis